THE ROLE OF STRATEGIC ALIGNMENT IN IMPROVING STRATEGIC DECISION AN APPLIED STUDY AT THE MINISTRY OF HEALTH HEADQUARTERS - Zahraa Basim Jaafar, Shehenaz Fadil Ahmed (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This current research aims to identify role of strategic alignment improving strategic decision, It research problem indicated that there is a weakness his been use of strategic alignment it, is clearly reflected in performance and its ability to face developments, specifically the field of technology, with clear weaknesses emerging in the strategic directions of managers , their neglect of this vital role to monitor and review all changes that may occur in the organization's business environment, which have an impact on the planning and implementation of its strategies, and the importance of research has emerged by providing possible solutions to problems , challenges it faces while performing its work according to the current research variables, and two hypotheses have been identified. There are several sub hypotheses for the purpose testing a relationship and influence between research variables. Two researchers have relied on descriptive isanalytical approach when presenting and collecting data and analyzing them. This research was conducted on Ministry of Health located in Bab Al-Moazam area and research community reached (208) managers, a form The questionnaire was a tool for collecting data. Exploratory and confirmatory factor analysis was conducted, and the validity and reliability of questionnaire was tested. There are (155) questionnaires this research sample, and the total of questionnaires valid for statistical analysis reached (140) forms. The current research Check a set of results, the most prominent of which was existence of positive relationship between strategic alignment and improving strategic decision.